RANCANG BANGUN PENGENDALI SUHU DAN KELEMBABAN RUNGAN BUDIDAYA JAMUR TIRAM MENGGUNAKAN ESP32 DAN SENSOR SHT22 - Topan, Paris; Indra Darmawan; Titi Andriani; Arjuna Satriawansyah (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
Oyster mushrooms are an agricultural commodity whose cultivation process still has obstacles that must be resolved, namely, the difficulty of cultivators in regulating the temperature and humidity in the oyster mushroom cultivation room. Usually oyster mushroom cultivators will water the cultivation room at certain times without considering the temperature and humidity conditions. so it can cause the room to have abnormal humidity values. To overcome this problem, a device was created that can water automatically by considering the temperature and humidity conditions in the cultivation room. This device consists of an ESP32 microcontroller, an SHT22 sensor which can read room temperature and humidity, a sprayer to spray water, and a fan whose job is to maintain the room temperature and humidity. The ESP32 device will be programmed to control two Single State Relays which function to turn the sprayer and fan on and off, based on temperature and humidity readings from the SHT22 sensor. The results of the research show that the designed device is able to maintain ideal temperature and humidity conditions for oyster mushrooms to grow, namely: The temperature value is in the range of 30°C - 35°C and humidity is between 70% - 100%.